Corporate Vulnerability and Bank Stability : Evidence from Jordan - Love, Inessa (2012)
This paper uses data on publicly listed companies in Jordan to evaluate corporate vulnerability and perform corporate stress testing. The exercise finds that both earnings and interest rate shocks have significant impact on corporate vulnerability. Because different banks have different sector exposures, and different sectors exhibit different vulnerability at different times, the stress tests that include corporate exposure will provide a more precise evaluation of bank soundness.